IDENTIFIKASI DAN PENENTUAN KADAR RESIDU INSEKTISIDA PADA KUBIS DAN TOMAT DI MODOINDING DAN RURUKAN - Oessoe, Yoakhim Y. E (EUGENIA, 2019)
This research aims to study 1) Maternal effect on the inheritance of yield components of Manado Yellow Use of Insecticides is one way that is very often made vegetable farmersto cope with pest and plant diseases. However, the use of insecticides may give negative effects for consumers of food containing residues of these poisons.Methodology of research is survey and laboratory. Collecting data in the survey was an interview of 20 vegetable farmers, each 10 from Modoinding and 10 from Rurukan that determined purposively. Laboratory data obtainedwith the ways to identify residues in the cabbage and tomatoes from Modoinding and Rurukan , using Gas Chromatography (GC) according to the analysis method of Pusat Pengujian Obat dan Makanan.Vegetable farmers in Modoinding and Rurukan often apply the insecticide organophospate and pyretroid on cabbage and tomato plants. The residues level in ccabbage and tomato from Modoinding and Rurukan far exceed the value of Acceptable Daily Intake of profonefos allowed.